A rare case of AIDS co-infected with COVID-19 presenting with disseminated Herpes zoster complicated with CMV and Varicella zoster virus meningoencephalitis - Daodu, Joseph; Basuli, Debargha; Parikh, Amish (Acta Biomedica Atenei Parmensis, 2022)
During the COVID-19 pandemic, numerous co-infections have been reported, with some studies indicating that patients with HIV/AIDS have worse outcomes when co-infected with COVID-19. Here, we present the case of a young adult male who presented with disseminated Varicella and was simultaneously diagnosed with AIDS and COVID-19 virus with several infection-related complications. A 25-year-old African-American male presented to the Emergency Department with vesicular, blistering rashes in multiple dermatomes including his eyelids. The screening test in the ED was positive for COVID-19. Given his high-risk sexual history, he was tested for HIV which returned positive with a CD4 count of zero. He was started on IV antivirals for disseminated varicella with zoster ophthalmicus. The patient was intubated for worsening respiratory failure and required intensive care. During the hospital course, he developed worsening encephalopathy and CSF analysis was positive for CMV and VZV. The patient has a prolonged hospital stay and exhibited evidence of infectious CNS vasculitis and HIV myelopathy. Anti-retroviral therapy was started after the acute period and the patient showed slow but definite clinical improvement.To the best of our knowledge, this is the first case report of a patient with AIDS with COVID-19 and disseminated VZV and with multiple complex infection-related complications.